Genome-Wide Analysis of GATA Transcription Factor Family in Quinoa (Chenopodium quinoa): Identification, Characterization, and Expression Profiles: Genome Survey of the GATA Transcription Factor in Quinoa - Le, Thi Man; La, Hong Viet; Chu, Ha Duc; Pham, Chau Thuy; Ha, Quyen Thi; Le, Thi Ngoc Quynh; Tran, Thi Thanh Huyen; Tran, Van Tien; Dong, Huy Gioi; Pham, Minh Hong; Tran, Vinh Thanh; Chu, Thi Bich Ngoc; Cao, Phi Bang (Journal of Tropical Life Science, 2024)
GATA-binding factor (GATA) proteins are the transcription factor (TF) family that are commonly involved in plant growth and development. The GATA TF family has been successfully identified and characterized for various higher plant species, but there is little research on the GATA TF family in quinoa (Chenopodium quinoa). In this present study, a total of 32 CqGATA genes were identified and analyzed in the quinoa genome. While the general features of the CqGATA TFs in quinoa were slightly variable, the majority of genes encoding the CqGATA TFs contained two and three exons. Our phylogenetic analysis demonstrated that the CqGATA TFs could be classified into four different groups. Gene expression analysis indicated that the expression profiles of the CqGATA genes varied in different tissues. Overall, our study could provide a reference for further functional characterization of the CqGATA genes in quinoa.